O celular como recurso pedagógico para um estudo sobre a relação das pessoas com o lugar: imagens do sujeito e o seu lugar - SOUSA, Alexsandro Costa de (2018)
The research entitled THE CELLPHONE AS A PEDAGOGICAL RESOURCE FOR A STUDY ON THE RELATIONSHIP OF PEOPLE WITH THE PLACE: images of the subject and one‟s place, focuses on the study of the place from a Phenomenological perspective of Perception by theorist Maurice Merleau-Ponty converging to the aspects of Humanistic Geography and Topophilia in Yi-Fu Tuan, proposal which aimed at addressing the geographical concept of place with the use of mobile technology - the cellphone - and the perceptions of the subject involved. The locus of this research has as its initial space a High School in São José de Ribamar city. The central objective of this study has been the construction of a manual and infographics using mobile technology to assist the teacher in developing the study of „place‟ as geography category, considering the relationships and perceptions of students from the first year of the High school through audiovisual images. Thus, following the assumptions of action research and intervention were developed several activities with the subjects of the research in a total of 40 students, these being: theoretical discussion, images documentation, production of videos, editing workshop on images and videos, interview with residents of the community. For data collection questionnaires were used with open-ended questions, interviews and observations, for the data analysis collected in light with the Phenomenology of Perception and the study of Topophilia, characterizing a qualitative research, based on theoretical contributions of Castells (2003), Lévy (1999), Milton Santos (2000), Eric Dardel (2015), Werther Holzer (1998), Marandola Jr. (2010), Moura (2010), Bottentuit Junior (2016), Merleau-Ponty (2006) among others. As final product the development of a didactic manual composed with infographics of the step by step on how to use mobile technology, a DVD which was produced by the students from places that represent aspects of the investigation on the place edited by the students involved in the research.